Adopting An Evidence-Based Management Approach In Teaching: Perspectives, Barriers And Enablers Among Academics In Business And Management - Tracz-Krupa, Katarzyna; Cassar, Vincent; Molek-Winiarska, Dorota; Bezzina, Frank (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This study investigates how business and management instructors in Central Europe comprehend and apply Evidence-Based Management (EBM) in their classrooms, the obstacles they face and the resources they require to adopt an EBM approach in their teaching. Thirty academics from three HEIs in Prague, Zagreb, and Opole answered a supervised, semi-structured questionnaire. Results showed that their view of EBM frequently differs from the mainstream definition, with a predilection for case studies, qualitative research, and readily available sources. Time constraints, a lack of instructional resources, and inadequate institutional support were salient obstacles. Access to resources, professional development, peer support, and local language content were critical facilitators. The findings are discussed, and the study provides practical recommendations to improve EBM integration in business and management education.